What is Japanese architecture? - Nishi, Kazuo (Kodansha International, 1985)
This book consists of the following many parts: the architecture of Buddhist temples and Shinto Shrines, residential and urban architecture, battle castles and castles towns, entertainment architecture in the Sukiya spirit.